Neoadjuvant chemotherapy prior to radical cystectomy for muscle‐invasive bladder cancer with variant histology. Issue 22 (25th July 2017) - Vetterlein, Malte W.; Wankowicz, Stephanie A. M.; Seisen, Thomas; Lander, Richard; Löppenberg, Björn; Chun, Felix K.‐H.; Menon, Mani; Sun, Maxine; Barletta, Justine A.; Choueiri, Toni K.; Bellmunt, Joaquim; Trinh, Quoc‐Dien; et al.
Abstract : BACKGROUND: Neoadjuvant chemotherapy in pure urothelial bladder cancer provides a significant survival benefit. However, to the authors' knowledge, it is unknown whether this benefit persists in histological variants. The objective of the current study was to assess the effect of neoadjuvant chemotherapy on the probability of non‐organ‐confined disease and overall survival after radical cystectomy (RC) in patients with histological variants. METHODS: Querying the National Cancer Data Base, the authors identified 2018 patients with histological variants who were undergoing RC for bladder cancer between 2003 and 2012. Variants were categorized as micropapillary or sarcomatoid differentiation, squamous cell carcinoma, adenocarcinoma, neuroendocrine tumors, and other histology. Logistic regression models estimated the odds of non‐organ‐confined disease at the time of RC for each histological variant, stratified by the receipt of neoadjuvant chemotherapy. Cox regression models were used to examine the effect of neoadjuvant chemotherapy on overall mortality in each variant subgroup. RESULTS: Patients with neuroendocrine tumors (odds ratio [OR], 0.16; 95% confidence interval [95% CI], 0.08‐0.32 [ P <.001]), micropapillary differentiation (OR, 0.30; 95% CI, 0.10‐0.95 [ P= .041]), sarcomatoid urothelial carcinoma (OR, 0.40; 95% CI, 0.17‐0.94 [ P= .035]), and adenocarcinoma (OR, 0.24; 95% CI, 0.06‐0.91 [ P= .035]) were less likely to harbor non‐organ‐confined disease at the time of RC when treated with neoadjuvant chemotherapy. An overall survival benefit for neoadjuvant chemotherapy was only found in patients with neuroendocrine tumors (hazard ratio, 0.49; 95% CI, 0.33‐0.74 [ P= .001]). CONCLUSIONS: Patients with neuroendocrine tumors benefit from neoadjuvant chemotherapy, as evidenced by better overall survival and lower rates of non‐organ‐confined disease at the time of RC. For tumors with micropapillary differentiation, sarcomatoid differentiation, or adenocarcinoma, neoadjuvant chemotherapy decreased the frequency of non‐organ‐confined disease at the time of RC. However, this favorable effect did not translate into a statistically significant overall survival benefit for these patients, potentially due to the aggressive tumor biology. Cancer 2017;123:4346‐55 . © 2017 American Cancer Society . Abstract : When evaluating the impact of neoadjuvant chemotherapy before radical cystectomy for patients with nonpure urothelial histological variants, only those patients with neuroendocrine tumors appear to experience an overall survival benefit. Patients with micropapillary differentiation, sarcomatoid urothelial tumors, and adenocarcinoma who receive neoadjuvant chemotherapy are less likely to harbor non‐organ–confined disease at the time of radical cystectomy, but do not appear to have an increased rate of overall survival.